Double‐counting challenges the accuracy of high‐latitude methane inventories. Issue 24 (29th December 2016) - Thornton, Brett F.; Wik, Martin; Crill, Patrick M.
Abstract: Quantification of the present and future contribution to atmospheric methane (CH4 ) from lakes, wetlands, fluvial systems, and, potentially, coastal waters remains an important unfinished task for balancing the global CH4 budget. Discriminating between these sources is crucial, especially across climate‐sensitive Arctic and subarctic landscapes and waters. Yet basic underlying uncertainties remain, in such areas as total wetland area and definitions of wetlands, which can lead to conflation of wetlands and small ponds in regional studies. We discuss how in situ sampling choices, remote sensing limitations, and isotopic signature overlaps can lead to unintentional double‐counting of CH4 emissions and propose that this double‐counting can explain a pan‐Arctic bottom‐up estimate from published sources, 59.7 Tg yr −1 (range 36.9–89.4 Tg yr −1 ) greatly exceeding the most recent top‐down inverse modeled estimate of the pan‐Arctic CH4 budget (23 ± 5 Tg yr −1 ). Plain Language Summary: Methane emissions from various places in the Arctic‐‐both on land and at sea‐‐have attracted increased attention in recent years. The increased attention is for several reasons, but one reason is that some of these Arctic methane sources were not known in the past. Another reason is that these Arctic methane sources may increase in size with a warming climate. However, discriminating between the influence of various onshore and offshore methane sources (wetlands, lakes, ponds, rivers, streams, and shallow seas) has proven difficult. We point out how overlaps in definitions and problems discriminating wetlands and small ponds may lead to double‐counting of some methane emissions in certain scenarios. Additionally, we show that some techniques used for discriminating methane sources are less effective than sometimes suggested. We suggest some ways our understanding of the various sizes of Arctic methane sources can be improved in the future. Key Points: Top‐down and bottom‐up estimates of the Arctic CH4 natural sources do not match; we suggest that double‐counting of emissions in bottom‐up accounting is a major cause of this discrepancy Double‐counting can occur due to overlap of wetland and lake or fluvial areas in models or inventories using low‐resolution maps Double‐counting can occur due to overlap of the δ 13 C‐CH4 property between many Arctic CH4 sources